2011
DOI: 10.1007/s00125-011-2098-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased mitochondrial substrate sensitivity in skeletal muscle of patients with type 2 diabetes

Abstract: Aims/hypothesis Mitochondrial respiration has been linked to insulin resistance. We studied mitochondrial respiratory capacity and substrate sensitivity in patients with type 2 diabetes (patients), and obese and lean control participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 37 publications
6
59
1
Order By: Relevance
“…One of the suggestions for the association could be the reduced aerobic capacity among the inactive co-twins (Leskinen et al 2010). However, although the number of mitochondria might be reduced in an insulin resistant skeletal muscle, the mitochondrial respiratory capacity can be maintained normal (Larsen et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…One of the suggestions for the association could be the reduced aerobic capacity among the inactive co-twins (Leskinen et al 2010). However, although the number of mitochondria might be reduced in an insulin resistant skeletal muscle, the mitochondrial respiratory capacity can be maintained normal (Larsen et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The results from the pilot study (respirometric measurements) are provided in Figures 2-4. The method we used has been described previously [12,16] . No differences were seen in mitochondrial substrate sensitivity for octanoyl carnitine between the groups and both groups increased their sensitivity for octanoyl carnitine in the trained leg (Figure 2A).…”
Section: High Intensity Trainingmentioning
confidence: 99%
“…In the past decade mitochondrial dysfunction in skeletal muscle has been linked to insulin resistance [3][4][5][6][7] , but an agreement has not been reached and the majority of data does not support this notion [8][9][10][11][12][13][14][15][16][17] . It has been shown that patients with type 2 diabetes have 30% lower mitochondrial content in their skeletal muscle compared to healthy control subjects [12,18] , and yet the intrinsic mitochondrial function (i.e., respiratory rates normalized for mitochondrial content) is similar in these two groups [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies examining respiration or fatty acid oxidation in isolated mitochondria or permeabilised muscle fibres, have reported that the functional capacity per mitochondrion in insulin resistant and/or type 2 diabetic subjects is similar or only very mildly reduced [85,88,91,[101][102][103] in insulin-resistant individuals, but when normalized to muscle mass, a substantial reduction is seen in insulin-resistant subjects [85,88,101]. These studies therefore only see marked differences when mitochondrial capacity is expressed per unit mass of skeletal muscle and thus indicate that in vivo mitochondrial defects observed with MRS may be more strongly related to reductions in mitochondrial number, than to substantial intrinsic mitochondrial defects.…”
Section: Mitochondrial Dysfunction In Muscle and Its Association Withmentioning
confidence: 99%